2017
DOI: 10.1016/j.ejogrb.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Association between vascular endothelial growth factor polymorphism and recurrent pregnancy loss: A systematic review and meta-analysis

Abstract: This meta-analysis showed that only rs1570360 (especially in Caucasians) and rs3025039 (especially in East Asians) may be risk factors for RPL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
2
12
0
2
Order By: Relevance
“…Although this probably reflects some variation in study characteristics, it is also important to note the inherent heterogeneity of patients with RPL. As demonstrated in other recent reviews on the topic (Jung et al, 2017;Sun et al, 2017), a myriad of underlying aetiologies that contribute to RPL make comparisons between study populations particularly challenging. Importantly, however, all the included studies excluded anatomical contributors to sperm fragmentation, such as varicocele, as well as several other factors such as body mass index, environmental exposures, caffeine and alcohol consumption, and smoking ( Supplemental TABLE 1).…”
Section: Discussionmentioning
confidence: 99%
“…Although this probably reflects some variation in study characteristics, it is also important to note the inherent heterogeneity of patients with RPL. As demonstrated in other recent reviews on the topic (Jung et al, 2017;Sun et al, 2017), a myriad of underlying aetiologies that contribute to RPL make comparisons between study populations particularly challenging. Importantly, however, all the included studies excluded anatomical contributors to sperm fragmentation, such as varicocele, as well as several other factors such as body mass index, environmental exposures, caffeine and alcohol consumption, and smoking ( Supplemental TABLE 1).…”
Section: Discussionmentioning
confidence: 99%
“…11 Specific gene polymorphisms and irregular gene expression are, in turn, recognized as two important risk factors in patients with idiopathic recurrent spontaneous miscarriage (IRSM). 12 Several studies have reported that VEGF polymorphisms and increased risk of IRSM were associated. 13,14 Similarly, other studies showed that abnormal expression of VEGF 15,16 and Cx43 9,10 were related to IRSM.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have suggested that multiple SNPs of VEGF gene increase the risk of diseases such as ovarian malignancies, hypertensive disorder of pregnancy, and idiopathic recurrent pregnancy loss, and thereafter have been confirmed by multiple meta-analyses. Our meta-analysis results revealed certain VEGF gene polymorphisms had a distinct different impact on the pathogenesis of PCOS in contrast to its role in the pathogenesis of other female reproductive system disorders [43][44][45]. There was a significant correlation between VEGF rs2010963 and decreased PCOS susceptibility, suggesting VEGF rs2010963 could be a protective factor for the risk of PCOS.…”
Section: Discussionmentioning
confidence: 73%